Association between first birth caesarean delivery and adverse maternal-perinatal outcomes in the second pregnancy: a registry-based study in Northern Tanzania - Raziya Gaffur; Bariki Mchome; Lyasimana Lithaneninn Ndaninginan; Benjamin Asubiojo; Michael Johnson Mahande; Eusebious Maro (BMC, 2022)
Abstract Background Caesarean delivery (CD) is the commonest obstetric surgery and surgical intervention to save lives of the mother and/or the new-borns. Despite been accepted as safe procedure, caesarean delivery has an increased risk of adverse maternal and fetal outcomes. The rising rate of caesarean delivery has been a major public health concern worldwide and the consequences that come along with it urgently need to be assessed, especially in resource limited settings. We aimed to examine the relationship between first birth caesarean delivery and adverse maternal and perinatal outcomes in the second pregnancy among women who delivered at a tertiary hospital in Northern Tanzania. Methods A retrospective cohort study was conducted using maternally-linked data from Kilimanjaro Christian Medical Centre. All women who had singleton second delivery between the years 2011 to 2015 were studied. A total of 5,984 women with singleton second delivery were analysed. Multivariable log-binomial regression was used to determine the association between first caesarean delivery and maternal-perinatal outcomes in the second pregnancy. Results Caesarean delivery in the first birth was associated with an increased risk of adverse maternal and perinatal outcomes in the second pregnancy. These included repeated CD (ARR 1.19; 95% CI: 1.05-1.34), pre/eclampsia (ARR 1.38; 95% CI: 1.06-1.78), gestational diabetes mellitus (ARR 2.80; 95% CI: 1.07-7.36), uterine rupture (ARR 1.56; CI: 1.05-2.32), peri-partum hysterectomy (ARR 2.28; CI: 1.04-5.02) and preterm birth (ARR 1.21; CI: 1.05-1.38). Conclusion Caesarean delivery in their first pregnancy had an increased risk of repeated caesarean delivery and other adverse maternal-perinatal outcomes in the following pregnancy. Findings from this study highlight the importance of devising regional specific measures to mitigate unnecessary primary caesarean delivery. Additionally, these findings may help both clinicians and women in deciding against or for trial of labor after previous caesarean delivery in an event of absent direct obstetric indication.